Efeito da ovariectomia no reimplante dentário: análise histomorfométrica e imunoistoquímica em ratas - Silva, Vanessa Ferreira da [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
Estrogen deficiency is a systemic alteration that is frequently encountered by dental surgeons in the clinic, and is caused during menopause and after ovariectomy. Considering the shortage of literature in the study of dento-alveolar trauma in individuals with systemic condition, the aim of this study was to analyze the repair process in immediate dental replanting and its possible association with this systemic alteration by immunohistochemical and histomorphometrical analysis. Rats were subjected to estrous cycle evaluation for 10 days. Forty animals with regular cycle were selected for the experimental study. The study consisted of two experimental groups: group I: sham rats, and group II: ovariectomy (OVX) rats. Two month after OVX or sham surgery, the upper right incisors of all animals were extracted and immediately reimplanted. Animals were euthanized 7 and 15 days after reimplantation. Both groups presented reintegration of the periodontal ligament on the bone surface and cement layer and at 15 days after reimplantation were observed external root resorption. The study concluded that there was no difference in the healing process of the immediately reimplanted teeth between the studied groups on the analysed periods

A deficiência de estrógeno é uma condição sistêmica com a qual o cirurgião dentista pode se deparar na clínica e que pode ser causada durante a menopausa e após ovariectomia. Considerando a escassez da literatura no estudo do traumatismo dento-alveolar em indivíduos com essa condição sistêmica, o objetivo do trabalho é analisar o processo de reparo do reimplante dentário imediato após ovariectomia por meio da análise histomorfométrica e imunoistoquímica. Ratas foram submetidas ao estudo do ciclo estral durante 10 dias e após esse procedimento foram selecionados para o estudo quarenta animais que apresentaram ciclo regular. Os animais foram submetidos à cirurgia de exposição dos ovários - grupo I sham e remoção dos ovários - grupo II ovariectomia (OVX). Após dois meses foi realizado a exodontia e reimplante dentário imediato. Os animais sofreram eutanásia 7 e 15 dias após o reimplante. Nos dois grupos houve reinserção do ligamento periodontal no tecido ósseo e cemento e presença de reabsorção radicular externa de superfície aos 15 dias. A análise histomorfométrica e imunoistoquímica mostrou que não houve diferença no processo de reparo do reimplante imediato entre as ratas OVX e as Sham nos períodos estudados
Keywords: Reimplante dentário; Ovariectomia; Imunohistoquímica; Tooth replantation